2020
DOI: 10.3390/w12010143
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Flow Field around Horizontal Cylinders with Scour Hole

Abstract: This study presents the results of an experimental investigation on the flow-structure interactions at scoured horizontal cylinders, varying the gap between the cylinder and the bed surface. A 2D Particle Image Velocimetry (PIV) system was used to measure the flow field in a vertical plane at the end of the scouring process. Instantaneous and ensemble-averaged velocity and vorticity fields, viscous and Reynolds stresses, and ensemble-averaged turbulence indicators were calculated. Longitudinal bed profiles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Vegetation on river banks and floodplains plays an extremely important role in mitigating the adverse anthropogenic effects on the environment [1][2][3][4][5], especially in the areas most affected by human alterations (presence of bridge piers and abutments, pipelines, etc.) [6][7][8]. However, vegetation can have a significant impact on the flow hydrodynamics, influencing the exchange of mass and momentum across the river section [4,[9][10][11], as well as on fluvial geomorphology, water quality, and biodiversity (e.g., [12,13]).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation on river banks and floodplains plays an extremely important role in mitigating the adverse anthropogenic effects on the environment [1][2][3][4][5], especially in the areas most affected by human alterations (presence of bridge piers and abutments, pipelines, etc.) [6][7][8]. However, vegetation can have a significant impact on the flow hydrodynamics, influencing the exchange of mass and momentum across the river section [4,[9][10][11], as well as on fluvial geomorphology, water quality, and biodiversity (e.g., [12,13]).…”
Section: Introductionmentioning
confidence: 99%
“…Water 2021, 13, x FOR PEER REVIEW 4 of 14 etation, bed roughness or man-made structures acting as an obstruction for the flow generate turbulence and affect the entire flow velocity distribution, modifying the turbulence behavior [30,31]. In Table 1, the hydraulic conditions of the experimental study are reported.…”
Section: Laboratory Experiments and Methodologymentioning
confidence: 99%
“…Nevertheless, they could represent a new dataset that, for instance, may be used for the calibration of advanced numerical models. In fact, as is known, vegetation, bed roughness or man-made structures acting as an obstruction for the flow generate turbulence and affect the entire flow velocity distribution, modifying the turbulence behavior [30,31].…”
Section: Laboratory Experiments and Methodologymentioning
confidence: 99%
“…Positive values of the vorticity indicate clockwise fluid motion; on the contrary, negative values refer to counterclockwise direction. Specifically, the rotational direction provides information about flow acceleration and deceleration in the near-bed flow: counterclockwise rotation induces flow acceleration, with a downward transport of momentum in the downstream direction; clockwise rotation causes flow deceleration, with upward transport of momentum in the upstream direction [25,26]. It is evident that the vorticity changes its signs alternatively in the flow layer affected by the presence of both vegetation and bed roughness.…”
Section: Time-averaged Flowmentioning
confidence: 99%